The extent of audit report lag in the Islamic banking institutions in Malaysia - Kaaroud, Mohamed Ahmed; Mohd Ariffin, Noraini; Ahmad, Maslina (2016)

(untitled)
Timeliness of financial reporting is a mirror of up-to-date financial information which is considered as the main driver for useful corporate financial reporting. The extent of audit report lag is found to be the most observable indicator for timely financial reporting because financial reports cannot be issued without being audited and verified (i.e. true and fair view) by the external auditors. The study aims to examine the extent of audit report lag in the Islamic banking institutions in Malaysia. From 112 annual report observations during 2008 to 2014, the findings of descriptive statistics show that almost all the Islamic banks are capable of producing audited financial reports within the stipulated time during the period under study. However, the findings also showed an increase in the mean ARL from 56 days in 2008 to 73 days in 2014. This may be due to the requirements of Shari’ah audit in Islamic banking institutions in Malaysia as required by the Bank Negara Malaysia through the issuance of Shari’ah gGovenance Framework in 2010, GP8-i (amended in 2012) and the Islamic Financial Services Act (2013). A part from contributing to the literature on financial reporting timeliness, this study provides a feedback for the regulator on the practice of financial reporting process in the Islamic banking institution in Malaysia.